Problem Argumentasi Pluralisme Agama: Penelitian - Mustafa, Sahidi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Pluralism is a doctrine that does not recognize the existence of absolute truth, or a doctrine that considers no view is true, or that all views equally are true. In many cases, pluralism is often equated with tolerance. In its relation to religion, pluralism is often seen as equality between one religion and another. The differences that exist in religions are only differences in the exoteric aspect, that is at the sharia level only, not in the esthetic aspect. In fact, pluralists, through religious pluralism aim to eliminates truth claims from each religion followers. Because truth claims are considered as a trigger of horizontal conflicts. The method used in this research is critical descriptive qualitative research with the type of library research. This article shows that the arguments are built by pluralists to justify religious pluralism are problematic, because they attempt to equalize all religions. Even though the aim is good, that is to eliminate religious conflict, religious pluralism is not the solution.